2022
DOI: 10.3389/fpubh.2022.967733
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of foot ulcers in diabetic patients in Punjab, Pakistan

Abstract: Diabetes-related foot ulceration is prevalent and disabling, usually resulting in the amputation of the limb. The mortality rate is significant, and healed ulcers frequently reoccur. The main purpose of this study was to explore the prevalence of foot ulcers and their associated factors among diabetic patients in Punjab, Pakistan. Multistage cluster random sampling procedure was applied to perform a cross-sectional analysis in the state of Punjab, Pakistan. A sample of 1,503 people with diabetes, including 504… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
3
5
2
1
Order By: Relevance
“…This could be attributed to a variety of factors. There is a higher male involvement in outdoor activities compared to females [36], and this heightens susceptibility to foot trauma and harm [41][42][43][44]. Contrary to our findings, studies from India, Pakistan and Malaysia reported that women had a higher risk of having DFU [42,44,45].…”
Section: Plos Onecontrasting
confidence: 99%
See 1 more Smart Citation
“…This could be attributed to a variety of factors. There is a higher male involvement in outdoor activities compared to females [36], and this heightens susceptibility to foot trauma and harm [41][42][43][44]. Contrary to our findings, studies from India, Pakistan and Malaysia reported that women had a higher risk of having DFU [42,44,45].…”
Section: Plos Onecontrasting
confidence: 99%
“…There is a higher male involvement in outdoor activities compared to females [36], and this heightens susceptibility to foot trauma and harm [41][42][43][44]. Contrary to our findings, studies from India, Pakistan and Malaysia reported that women had a higher risk of having DFU [42,44,45]. A reason for this can be that in some areas of Africa and South Asia, particularly in some developing nations, prevailing socio-cultural beliefs restricted women from achieving higher levels of education compared to men.…”
Section: Plos Onecontrasting
confidence: 99%
“…The gender of the diabetic patients was provided in all papers. Regarding methodological quality bias, seven studies ( 27 , 29 – 32 , 35 , 36 ) had a low risk of bias, five studies ( 13 , 14 , 28 , 33 , 34 ) had a moderate level, and none had a high risk of bias. The authors' agreement on the retrieved data was strong (Kappa score = 0.82, p = 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…These articles included only Pakistani nationals, with sample sizes ranging from 230 (32) to 2199 (29), with a median of 1503 diabetic patients. Seven studies were conducted in Punjab province (13,14,30,(33)(34)(35)(36), three studies were performed in Sindh (27-29), one was conducted in Azad Kashmir (31), and one study was conducted nationwide (32). Regarding the study design, a cross-sectional research design was utilized in 10 of the 12 studies; one study employed casecontrol, and the other used a prospective research design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation